2013
DOI: 10.3892/mmr.2013.1684
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the expression of atrial calpains in electrical and structural remodeling during aging and atrial fibrillation

Abstract: Abstract. The aim of this study was to investigate the correlation between the change in the expression of atrial calpains and electrical, molecular and structural remodeling during aging and atrial fibrillation (AF). Adult and aged canines in sinus rhythm (SR) and with persistent AF (induced by rapid atrial pacing) were investigated. A whole-cell patch clamp was used to measure the L-type Ca 2+ current (I Ca-L ) in cells in the left atrium. The mRNA and protein expression of the L-type calcium channel alc sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Previous studies have shown that activated calpain mediated the degradation of myofibrillar structure [27], cardiomyocyte loss [28] and I Ca, L reduction [29] in the pressure-overloaded feline myocardium and atrial fibrillation models. Given our results showing structural and electrical remodelling in the paced VCMs, we hypothesized that the inhibition of calpain may attenuate the adverse effects of pacing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that activated calpain mediated the degradation of myofibrillar structure [27], cardiomyocyte loss [28] and I Ca, L reduction [29] in the pressure-overloaded feline myocardium and atrial fibrillation models. Given our results showing structural and electrical remodelling in the paced VCMs, we hypothesized that the inhibition of calpain may attenuate the adverse effects of pacing.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that activated calpain mediated the degradation of myofibrillar structure [27], cardiomyocyte loss [28] and I Ca, L reduction [29], we hypothesized that the inhibition of calpain may attenuate the adverse effects of pacing. Cardiac troponin T was reported to be a marker of cardiomyocytes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Other ECM macromolecules (i.e., glycoproteins, proteoglycans) are, at this time, degraded by neutral protease activity [83]. However, protocols using a primary digestion with protease, only later employing collagenase have been described [84], as have protocols using collagenase alone [85,86].…”
Section: Enzymatic Digestionmentioning
confidence: 97%
“…Changes in atrial electrophysiology and structure, referred to as remodeling, constitute the primary features of AF occurrence, maintenance and recurrence (6,7). Changes in ion currents, including Ca 2+ and K + , form the basis for early electrical remodeling in AF (8,9).…”
Section: Introductionmentioning
confidence: 99%